PENGARUH PROFITABILITAS, LIKUIDITAS, DAN AKTIVITAS TERHADAP NILAI PERUSAHAAN MANUFAKTUR - aprilia dewi kumala; rohmad fuad armansyah (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
ABSTRACT. The purpose of this research is to find out the effect of profitability, liquidity, and activity on the value of manufacturing companies listed on the IDX. Researchers use a period of 3 years with a time span of 2018-2021. This study uses a quantitative approach. The sampling technique is purposive sampling, so that the sample used is 52 manufacturing companies listed on the IDX for the 2018-2021 period. The data analysis used is multiple regression assisted by the SPSS 25 application. This test shows that profitability has a significant positive effect on firm value, while liquidity and activity have no significant effect on firm value